Early Mesoproterozoic (1.6-1.5 Ga) granulite facies events in the Ongole domain: geodynamic significance and global correlation - Sarkar, Tapabrato; Schenk, Volker (Journal of metamorphic geology, 2016)
The late Palaeoproterozoic to early Mesoproterozoic Ongole domain of the Eastern Ghats Belt in southeastern India is composed of a suite of charnoenderbites with enclaves of metapelitic and mafic granulites. Geochemical data for all meta-igneous rocks are typical for continental magmatic arc suites.
Gesehen am 12.05.2020